Effect of vermicompost and organic fertilizer on the growth, yield, and quality of lettuce (Lactuca sativa L.) - Sriwichan, Yotsanon; Kaewsith, Sakda; Phrophayak, Julalak (Food Agricultural Sciences and Technology, 2026)
This experiment aimed to investigate the effects of vermicompost and different rates of organic fertilizer on the growth, yield, and quality of organic lettuce (Lactuca sativa L.). A Completely Randomized Design was employed with nine treatments, four replications, and ten plants per replication. The study was conducted from January to June 2023 at the nursery of the Landscape Management Division, Building and Facilities Office, Mahasarakham University. The results indicated that the application of vermicompost and organic fertilizer significantly increased soil nutrient availability, including nitrogen, phosphorus, potassium, organic matter, and cation exchange capacity (CEC). Lettuce grown with the application of organic fertilizer at the rate of 38.7 g plant-1 showed the largest improvement in growth and yield characteristics, including stem diameter, number of leaves, fresh weight, and dry weight. Furthermore, this treatment resulted in the highest levels of lettuce quality attributes, particularly total soluble solids and chlorophyll content.